2017
DOI: 10.1155/2017/5762172
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Flavonoids and Their Relationship with Oxidative Stress

Abstract: Depression is a serious disorder that affects hundreds of millions of people around the world and causes poor quality of life, problem behaviors, and limitations in activities of daily living. Therefore, the search for new therapeutic options is of high interest and growth. Research on the relationship between depression and oxidative stress has shown important biochemical aspects in the development of this disease. Flavonoids are a class of natural products that exhibit several pharmacological properties, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
98
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(99 citation statements)
references
References 146 publications
(148 reference statements)
1
98
0
Order By: Relevance
“…The results showed that it contained many different active constituents, such as chlorogenic acid and isoorientin. Previous studies reported that flavonoids contributed to the pharmacological activities and showed antidepressant effects, as well as antioxidant effects ( Hritcu et al, 2017 ). Chlorogenic acid is a polyphenol found in plant families, which suggests that the antidepressant-like effects are mediated through decrease immobility time in the tail suspension test and the FST ( Park et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that it contained many different active constituents, such as chlorogenic acid and isoorientin. Previous studies reported that flavonoids contributed to the pharmacological activities and showed antidepressant effects, as well as antioxidant effects ( Hritcu et al, 2017 ). Chlorogenic acid is a polyphenol found in plant families, which suggests that the antidepressant-like effects are mediated through decrease immobility time in the tail suspension test and the FST ( Park et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many phenylpropanoids and flavonoids are involved in the responses to oxidative stress [14][15][16] , drought stress 17 , and disease resistance [18][19][20][21] . In Vitis vinifera, genes related to phenylpropanoid metabolism have been found to be less induced and/or more repressed in drought-sensitive rootstocks 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenols are the major constituents of herbal medicine having multifaceted biological actions [86], such as phenolic acids which boost up the brain antioxidant status by scavenging wide range of ROS and metal ions, which also inhibit signaling system of inflammation and its key inflammatory mediators, thus improving anxiety and depression [87]. Besides, flavonoids are the class of compounds which suppress oxidative nitrosative-stress, attenuate neuroinflammation, potentiate GABA A receptor-Cl ion channel complex, increase monoamines, serotonin, and dopamine levels in the CNS, and also modulate monoaminergic neurotransmitter [88]. In our previous research, we revealed that MEHC can effectively suppress in both central and peripheral nociception pathways, which prove that the bioactive compounds of MEHC can act on the central nervous system by crossing the blood brain barrier (BBB).…”
Section: Quantitative Phytochemical Analysismentioning
confidence: 99%